The Differences in Regulation of Emotions Based on Age Range and Gender in Adolescents at Uswatun Khasanah Orphanage Samarinda - Muhammad Bachtiar safrudin (Universitas Muhammadiyah Kalimantan Timur, 2021)
Adolescence shows changes in emotional characteristics that tend to be unstable, where adolescence is considered a period of hurricane storms. Changes in the stages of this developmental body when viewed from the characteristics, it is not known for sure whether there are differences between groups of male and female adolescents and the age level (early, middle and late) in these adolescents. This study aims to describe the picture and determine the differences in emotional regulation in terms of gender and age range in adolescents at the Uswatun Khasanah Orphanage in Samarinda. The research respondents were 104 which were divided by gender and age range. This study uses emotion regulation instruments that refer to standard research and tools. This research approach uses quantitative descriptive-comparative research. The results showed that there were differences in the emotional regulation of gender in adolescents at the Uswatun Khasanah in Samarinda orphanage with a value of sig (2 tailed) = 0.000. Other results show that there are differences in emotional regulation with values ​​of sig (2 tailed) = 0.005, 0.001 and 0.000 in terms of the age range of early, middle and late adolescents at the Uswatun Khasanah Orphanage. Recommendations for further research to compare groups of adolescents who are in orphanages and adolescents who live with their parents, with a larger and more evenly distributed number of respondents, are important suggestions for future research